PENGEMBANGAN DESA CIHERANG KABUPATEN BANDUNG SEBAGAI DESA WISATA RINTISAN: - Lazuardina, Annisa; Novianti, Evi; Sihombing, Jimmy R.; Baitulloh, Taqiy Gusdi; Risda, Irfan Taufik; Fadilah, Siti Nur; Burhanudin, Cep Bubun (Warta Pariwisata, 2025)
The development of Ciherang Tourism Village in Bandung Regency as a pioneering tourism village aims to maximize its natural, cultural, and artificial potential. Using SWOT analysis, this study identified strengths such as natural and cultural wealth, weaknesses in the form of lack of potential management, opportunities in developing superior tourism, and threats from competition and environmental risks. This study also emphasizes the importance of the role of Local Champions, such as Pokdarwis, in managing destinations and empowering communities. With an integrated approach, workshops, and infrastructure support, Ciherang Tourism Village has great potential to develop into a competitive independent tourism village.